Socio-economic Features of Womenfolk of Indian Sunderbans Involved in Fish Drying - Aparna Roy , A. P. Sharma , Utpal Bhaumik , Arun Pandit , S. R. K Singh , S. Saha; A. Mitra (Indian Journal of Extension Education, 2017)
Indian Sundarbans population in many ways face additional burdens because of poor communications resulting from the innumerable creeks, canals and tidal rivers, which separate the islands from each other and from the mainland. Gender discrimination is common throughout the region. Women have to work harder to secure food and livelihood. They have less control over income and assets and are being subjected to violence and intimidation; subordinate social position; poorly represented in policy and decision making. For women engaged in fry collection and fish drying/processing, the problems are compounded by extreme poverty, poor housing, health and sanitation, limited access to safe drinking water, low literacy rates, limited access to support services, resource opportunities and social exclusion. Women at Sunderban often involved in fish drying for four months as they have no other viable alternative livelihood. Astudy was conducted in Frezarganj areas of Sunderban in Kalistan and Baliara char two important dry fish business centre where 200 fish dry workers were interviewed personally. The study revealed that the dry-fish women workers belong to backward community. More than 50 per cent of fisher women is Sunderban belong to families living in abject poverty. The money they earn is essential for the subsistence of their families. About 87 per cent of the dry fish workers are illiterate. The sorting and drying of fish work performed by the women workers. They are engaged on the basis of daily wages. They get ` 150 per day. They work from morning to evening, about8 hours a day with a break of one hour for midday meal. The women dry fish workers involved in fish drying/processing for their livelihood during the winter season from middle of October to middle of February. During these period the monthly average income of a dry fish worker become ` 3000/- per month. Most of the women dry fish workers belong to low income group (66 %). Significant number of women dry fish workers (37 %) reported that they are engaged in as because they have no other viable alternative. Thus it is necessary to empower women fishers in the trade to uplift their socio-economic status.